Some experimental aspects of absolute configuration determination using single crystal X-ray diffraction. Issue 10 (15th October 2017) - Thompson, Amber L.; Jenkinson, Sarah F.; Fleet, George W.J.
Graphical abstract: Abstract: Students of single crystal X-ray diffraction are often give advice as to how best to collect their data when attempting absolute configuration determination. These 'rules' often have more grounding in gut-feeling than evidence. Thus, in an effort to provide advice and evidence that today's crystallographers can pass onto to tomorrow's young scientists, we present a systematic study of 1-deoxy-l -arabinitol, a straight chain sugar which crystalises well in the space group I 4 1 .